Pricing Strategies and Implementation Promotion Strategies to Improve Customer Loyalty - Kuncoro, Amin; Sutomo, Y. (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2018)
This study aims to analyze pricing and promote strategies to increase customer loyalty of sharia banks in Kudus, Central Java, Indonesia. This research method using qualitative and quantitative approach. The data used is time series data. The population of this study are customers who actively transact in Islamic banks in Kudus. Sampling technique using non probability sampling with accidental type of sampling. So the number of respondents needed in this research is a number of 100 active bank customers. The analytical method uses correlational descriptive analysis using Structural Equation Modeling (SEM), correlational assumption test and classical assumption test using AMOS 20 software. The result of this research explains that price and promotion contribute to increase customer and product loyalty which can become empirical variable. This proves that Sharia Bank is expected to have a special strategy to increase customer loyalty. How to increase loyalty in addition to improving the quality of Islamic banking products such as murobahah, musyarokah and mudharobah is to improve the characteristics of macro and Sharia micro finance institutions. This is because the excess of syariah bank products has never been found in conventional financial institutions in Indonesia.